2013
DOI: 10.1111/tbed.12154
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of a Highly Pathogenic Type 2 Porcine Reproductive and Respiratory Syndrome Virus: Analyses of Envelope Protein-Coding Genes

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) has long been an economically devastating swine viral disease. The recent emergence of a highly pathogenic type 2 PRRSV with high mobility and mortality in China, spreading in Vietnam, Laos, and Thailand has placed neighbouring countries at risk. This study applied a codon-based extension of the Bayesian relaxed clock model and the fixed effects maximum-likelihood method to investigate and compare the evolutionary dynamics of type 2 PRRSV for all of k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This result might be due to the high substitution rate detected in the ORF5 gene. In addition, the substitution rate in the ORF5 gene of the Vietnamese strains, which was 4459 × 10 −3 , was slightly faster than the substitution rates observed in common type II PRRSV strains [31] This supports our hypothesis. According to our analysis, the T MRCA of sub-lineage 5.1 strains was approximately 17 years ago, which is supported by serological evidence for anti-PRRSV antibodies in Vietnam during this time.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…This result might be due to the high substitution rate detected in the ORF5 gene. In addition, the substitution rate in the ORF5 gene of the Vietnamese strains, which was 4459 × 10 −3 , was slightly faster than the substitution rates observed in common type II PRRSV strains [31] This supports our hypothesis. According to our analysis, the T MRCA of sub-lineage 5.1 strains was approximately 17 years ago, which is supported by serological evidence for anti-PRRSV antibodies in Vietnam during this time.…”
Section: Discussionsupporting
confidence: 79%
“…Nguyen et al [31] can not conclude the role of selected position in typical PRRSV and HP-PRRSV. In this study, our analysis of sites under selective pressure indicated that most of the sites undergoing positive selection (amino acids 33, 34, 35, 58, and 59) are located in ecto-domain 1, which contains the linear epitope, and an additional positive selection site is also predicted in ecto-domain 2 (amino acid 104).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-passage Madin-Darby canine kidney (MDCK) cells were maintained in DMEM containing 10% fetal bovine serum (FBS). Influenza viruses Re-5 [ 22 ], Re-6 [ 23 ], and Re-9 were provided by the National Animal Influenza Reference Laboratory. Viruses were generated with a “6 + 2” strategy: all three viruses contained 6 internal genes from A/Puerto Rico/8/1934 (H1N1).…”
Section: Methodsmentioning
confidence: 99%
“…The infection of pigs of all ages featured by high fever (41-42°C), high morbidity (50%-100%) and mortality (20%-100%) was initially addressed as “swine high fever disease (SHFD)” [ 24 , 25 ]. In the next couple of months, the disease spread to most provinces of China and some other Asian countries such as Mongolia, Vietnam, Thailand, India, and Laos [ 26 - 30 ]. The outbreak of HP-PRRSV resulted in a dramatic decline of pig stock and high prices of pork meat in China [ 31 ].…”
Section: General Situation Of Prrsv In Chinamentioning
confidence: 99%